Penerapan Model Pembelajaran Saintifik untuk Meningkatkan Pemahaman Konsep Ilmu Pengetahuan Alam Siswa Sekolah Menengah Pertama - Yulianti Yulianti (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The purpose of this study was to describe students' understanding of scientific concepts in science lessons which illustrate the teacher's ability to direct learning through a scientific learning model for class IX students of SMP Negeri 1 Taliwang. In the science learning process, teachers tend to use the lecture method when learning and are one-way only, as a result, student learning outcomes tend not to meet the Minimum Completeness Criteria. The type of this research is Classroom Action Research (CAR) which was adopted by Kemmis and Mc. Taggart has been implemented in two cycles. The research subjects were 31 Class IX students of SMP Negeri 1 Taliwang. This classroom action research was carried out in two cycles, each cycle consisting of planning, action, observation, and reflection stages. The results showed that the average ability of students' understanding of concepts was 76.58 in the first period (cycle 1) and the success rate increased to 81.87 in the second period (cycle II). Based on the results of the study, it can be concluded that the application of scientific learning to science lessons in Class IX can improve students' conceptual understanding of SMP Negeri 1 Taliwang.